A life course perspective on the income-to-health relationship: Macro-empirical evidence from two centuries - Korbinian Nagel (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
The epidemiological literature discusses two contrary hypotheses that describe life course variations in the income-to-health relationship: the cumulative advantage and the age as leveller hypothesis. Since related micro level studies are criticised due to an income-rank effect, this study transfers the investigation of both hypotheses to a macro level with a long time horizon. It asks whether increases in per capita income improve population health and whether the improvements differ across population age groups. The analysis uses an unbalanced panel data set with 20 countries and up to 211 years, and relies on an error correction and common factor framework to investigate the long-run equlibrium relationship between income and selected measures of age specific population health. A significant effect of per capita income on survival rates is found for middle ages but not for very young and for old ages. From this it can be concluded that while the cumulative advantage theory describes the transition from young to middle ages, the transition from middle to old ages corresponds to the age as leveller mechanism.
Keywords: J11; C22; I15; 330; Population Health; Economic Development; Panel Time Series Analysis; Cumulative Advantage; Age as Leveller